PENDIDIKAN KESEHATAN PENCEGAHAN DAN PENGENDALIAN PENYAKIT DIABETES DI WILAYAH KERJA PUSKESMAS MUARA RAPAK BALIKPAPAN - Rahmawati Shoufiah; Rus Andraini (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Diabetes mellitus (DM) is a metabolic disorder characterized by increased blood glucose levels (hyperglycemia) due to damage to insulin secretion and insulin action2. Conditions in Muara Rapak Village, diabetes is one of the diseases with the highest coverage of non-communicable diseases. Data from 01 January 2023 to 31 December 2023, the number of cases of diabetes mellitus sufferers was 728 people9. Health education activities to prevent and control diabetes mellitus aim to increase public knowledge about the symptoms and risks as well as ways to prevent and control diabetes mellitus so as to reduce the risk of diabetes mellitus for individuals, families and those around them. This community service activity was carried out from April to August 2024 in the working area of ​​the Muara Rapak Balikpapan Community Health Center. The method of this activity is health education in the community and assistance to diabetes mellitus sufferers by providing health education and monitoring blood sugar for sufferers, and as a follow-up effort to continue the activity, cadre training activities are held. The outcomes of this community service activity include an increase in knowledge with the average knowledge of participants before education being 47.6% and after education being 91.5% with an average increase in knowledge of 43.9%, apart from that, based on the results of observations of blood sugar in diabetes mellitus sufferers, it can be seen that there has been a decrease average blood sugar in diabetes mellitus sufferers, and other outcomes were obtained in the form of hypertension booklets, IPR booklets and activity videos